Revision and taxonomic position of the genus Euphronia Martius ex Martius & Zuccarini (Vochysiaceae) - Lleras, Eduardo (Acta Amazonica, 1976)
In this paper the generic name Euphronia Martius ex Martius & Zuccarini is recognized as the valid name for what has commonly been known as Lightia Rob, Schomburgk. The taxonomic position of the genus has been reconsidered, and Euphronia has been removed from the Trigoniaceae, and placed in the Vochysiaceae with which its affinities are closest. Only one species has been recognized, due to the high variability in size and shape of the leaves.